Development of novel miRNA-based vaccines and antivirals against Enterovirus 71 - Yee, Isabel Pin Tsin *; Poh, Chit Laa * (Bentham Science Publishers, 2016)

(untitled)
The Hand, Foot and Mouth Disease (HFMD) is caused by Enterovirus 71 (EV-A71) and Coxsackie viruses. Common HFMD symptoms are high fever (≥ 39oC), rashes, and ulcers but complications due to virulent EV-A71 may arise leading to cardiopulmonary failure and death. The lack of vaccines and antiviral drugs against EV-A71 highlights the urgency of developing preventive and treatment agents. Recent studies have reported the emergence of novel antiviral agents and vaccines that utilize microRNAs (miRNAs). They belong to a class of small (19-24 nt) non coding RNA molecules. As miRNAs play a major role in the host regulatory system, there is a huge opportunity for interplay between host miRNAs and EV-A71 expressions. A total of 42 out of 64 miRNAs were up-regulated in EV-A71-infected cells. There was consistent up-regulation of miR-1246 gene expression that targeted the DLG3 gene which contributes to neurological pathogenesis. In contrast, miR-30a that targets calcium channels for membrane transportation was down-regulated. This leads to repression of EV-A71 replication. The impact of host miRNAs on immune activation, shutdown of host protein synthesis, apoptosis, signal transduction and viral replication are discussed. miRNAs have been used in the construction of live attenuated vaccines (LAV) such as the poliovirus LAV that has miRNA binding sites for let-7a or miR-124a. The miRNA-bearing vaccine will not replicate in neuronal cells carrying the corresponding miRNA but could still replicate in the gastrointestinal tract and hence remains to act as immunogens. As such, miRNAs are attractive candidates to be developed as vaccines and antivirals.